Work Matters : How Parents' Jobs Shape Children's Well-Being - Perry-Jenkins, Maureen, 1959- (Book collections on Project MUSE., 2022)
"How new parents in low-wage jobs juggle the demands of work and childcare, and the easy ways employers can helpLow-wage workers make up the largest group of employed parents in the United States, yet scant attention has been given to their experiences as new mothers and fathers. Work Matters brings the unique stories of these diverse individuals to light. Drawing on years of research and more than fifteen hundred family interviews, Maureen Perry-Jenkins describes how new parents cope with the demands of infant care while holding down low-wage, full-time jobs, and she considers how managing all of these responsibilities has long-term implications for child development. She examines why some parents and children thrive while others struggle, demonstrates how specific job conditions impact parental engagement and child well-being, and discusses common-sense and affordable ways that employers can provide support.In the United States, federal parental leave policy is unfunded. As a result, many new parents, particularly hourly workers, return to their jobs just weeks after the birth because they cannot afford not to. Not surprisingly, workplace policies that offer parents flexibility and leave time are crucial. But Perry-Jenkins shows that the time parents spend at work also matters. Their day-to-day experiences on the job, such as relationships with supervisors and coworkers, job autonomy, and time pressures, have long-term consequences for parents' mental health, the quality of their parenting, and, ultimately, the health of their children.An overdue look at an important segment of the parenting population, Work Matters proposes ways to reimagine low-wage work to sustain new families and the development of future generations"--